Real‐Time Oceanographic Data: From Safety to Science. Issue 34 (26th August 2014) - Meyers, Steven D.; Scudder, Jeffrey; Luther, Mark E.
<x xml:space="preserve">Abstract</x> Coastal areas such as bays and estuaries host 30%–50% of the global human population and shipping ports that handle 80% of world trade. These areas are increasingly vulnerable to chemical and biological contamination and to storm surge in the short term and to sea level rise in the long term.